TIPE1 Suppresses Growth and Metastasis of Ovarian Cancer. (4th June 2021) - Zhang, Zhenyu; Chang, Minghui; Song, Xingguo; Wang, Kangyu; Sun, Wenjuan; Ma, Hongxin; Yan, Xiaohui; Sun, Yuhong; Song, Xianrang; Xie, Li
Abstract : TIPE1, a newly identified member in TIPE (TNFAIP8) family, plays an important role in tumorigenesis and immune regulation, but its role in ovarian cancer, especially in tumor metastasis, remains unknown. In the current study, we aimed to reveal the protein expression spectrum of TIPE1 in normal human tissues and explored its relationship with metastasis in ovarian cancer. The results of IHC staining showed that TIPE1 protein was not only detected in cytoplasm in most human tissues but also expressed in both cytoplasm and nucleus in squamous epithelium and some epithelial-derived cells with secretory functions, such as esophagus, cervix uteri and ovary, and thyroid gland. Moreover, TIPE1 protein was downregulated in ovarian cancer tissues compared with that in the paracancerous. More importantly, TIPE1 suppressed tumorigenesis and metastasis of ovarian cancer in vitro and in vivo, as evidence shows its ability to suppress growth, colony formation, migration, and epithelial-mesenchymal transition (EMT) of ovarian cancer. Taken together, our results demonstrate the suppressor role of TIPE1 in ovarian cancer metastasis, indicating TIPE1 might be a metastasis predictor and a novel therapeutic target for ovarian cancer.